Landslide Risk Mapping for Sustainable Tourism Development: A Case Study in Kalibaru Watershed, Indonesia - Bachri, Syamsul; Aksa, Furqan; Cahyaning Putri, Nanda Regita; Hakiki, A Riyan Rahman; Heni Prastiwi, Mellinia Regina; Hidiyah, Tabita May; Sumarmi, Sumarmi (Universitas Negeri Medan, 2025)
The development of sustainable tourism in landslide-prone areas required a detailed understanding of environmental risks to ensure safety and resilience. This study aimed to generate a comprehensive landslide risk map to support sustainable tourism development in the Kalibaru Watershed, located in the Raung Volcano region of Indonesia. This study employed the Spatial Multi-Criteria Evaluation (SMCE) method using spatial data and GIS software to map landslide risk based on three main components: hazard, vulnerability, and capacity. The results classified landslide risks in the Kalibaru Watershed into three categories: high risk (21,682 hectares), medium risk (28,113 hectares), and low risk (22,742 hectares). The findings revealed that the highest risk areas were concentrated on the middle and upper slopes of the watershed, particularly within the Glenmore and Kalibaru sub-districts, where a combination of steep terrain, soil characteristics, and heavy rainfall exacerbated landslide susceptibility. This risk map provided valuable insights for stakeholders involved in sustainable tourism planning, offering a strategic tool for developing safe, environmentally-conscious, and disaster-resilient tourism infrastructure. The implementation of this map aimed to raise awareness among local communities and policymakers about the potential landslide risks and encouraged the adoption of effective mitigation measures, fostering a more sustainable and disaster-aware tourism model in the region.